1983
DOI: 10.1111/j.1365-2052.1983.tb01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine marker genes: Polymorphism for plasminogen

Abstract: SummaryPolymorphism for two autosomal alleles of equine plasminogen, PLG1 and PLG2, was demonstrated in plasma by isoelectric focusing and immunofixation, with a goat anti‐human plasminogen antibody. The frequency of PLC2 was 0.16 in 150 Standardbreds, 0.20 in 96 Thoroughbreds, and 0.39 in 32 Shetland ponies. No evidence for linkage of PLG with any of 13 marker loci was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…It was suggested that the Eso allele either changes the enzymatic characteristics of esterase with regard to substrates and inhibitors, or that it gives rise to an enzymatically inactive protein (Gahne 1966). Weitkamp (1987) described a silent allele for a minor red cell protein of unknown function and identity in equine. Likewise in the present study the X" allele may be assumed to be recessive, possibly as a consequence of a defective or absent substance whose phenotypic effect can be masked in the heterozygote by the functioning X 1 and X 2 substances.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the Eso allele either changes the enzymatic characteristics of esterase with regard to substrates and inhibitors, or that it gives rise to an enzymatically inactive protein (Gahne 1966). Weitkamp (1987) described a silent allele for a minor red cell protein of unknown function and identity in equine. Likewise in the present study the X" allele may be assumed to be recessive, possibly as a consequence of a defective or absent substance whose phenotypic effect can be masked in the heterozygote by the functioning X 1 and X 2 substances.…”
Section: Discussionmentioning
confidence: 99%
“…For horses from which only plasma samples were available, PGM was typed from plasma using the IEF system of Gahne et al (1980), stained with the same reagents used for typing red cell PGM. Plasminogen (PLG) was typed as described by Weitkamp et al (1983). Malic enzyme (ME1 ) was typed in either red cells or plasma by the procedures referenced in Weitkamp et al (1982a).…”
Section: Genetic Marker Typingmentioning
confidence: 99%